Reliable and valid NEWS for Chinese seniors: measuring perceived neighborhood attributes related to walking - Lee Lok-chun; Ho Sai-yin; Cheung Man-chin; Sit Cindy HP; Cerin Ester; Chan Wai-man (BMC, 2010)
Abstract Background The effects of the built environment on walking in seniors have not been studied in an Asian context. To examine these effects, valid and reliable measures are needed. The aim of this study was to develop and validate a questionnaire of perceived neighborhood characteristics related to walking appropriate for Chinese seniors (Neighborhood Environment Walkability Scale for Chinese Seniors, NEWS-CS). It was based on the Neighborhood Environment Walkability Scale - Abbreviated (NEWS-A), a validated measure of perceived built environment developed in the USA for adults. A secondary study aim was to establish the generalizability of the NEWS-A to an Asian high-density urban context and a different age group. Methods A multidisciplinary panel of experts adapted the original NEWS-A to reflect the built environment of Hong Kong and needs of seniors. The translated instrument was pre-tested on a sample of 50 Chinese-speaking senior residents (65+ years). The final version of the NEWS-CS was interviewer-administered to 484 seniors residing in four selected Hong Kong districts varying in walkability and socio-economic status. Ninety-two participants completed the questionnaire on two separate occasions, 2-3 weeks apart. Test-rest reliability indices were estimated for each item and subscale of the NEWS-CS. Confirmatory factor analysis was used to develop the measurement model of the NEWS-CS and cross-validate that of the NEWS-A. Results The final version of the NEWS-CS consisted of 14 subscales and four single items (76 items). Test-retest reliability was moderate to good (ICC > 50 or % agreement > 60) except for four items measuring distance to destinations. The originally-proposed measurement models of the NEWS-A and NEWS-CS required 2-3 theoretically-justifiable modifications to fit the data well. Conclusions The NEWS-CS possesses sufficient levels of reliability and factorial validity to be used for measuring perceived neighborhood environment in Chinese seniors. Further work is needed to assess its construct validity and generalizability to other Asian locations. In general, the measurement model of the original NEWS-A was generalizable to this study context, supporting the feasibility of cross-country and age-group comparisons of the effect of the neighborhood environment on walking using the NEWS-A as a tool to measure the perceived built environment.